Magnetic recording medium with oxidized seed layer
By introducing an oxidized seed layer into the magnetic recording medium, the traditional media has solved the shortcomings in thermal stability and response characteristics, and achieved high signal-to-noise ratio and excellent data storage reliability, which is suitable for a variety of magnetic recording technologies.
Patent Information
- Application Number
- CN202510632041.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-16
- Publication Date
- 2025-08-29
AI Technical Summary
Traditional magnetic recording media have shortcomings in high-density recording, thermal stability and high-frequency response, and it is difficult to meet the multiple needs of data storage at the same time.
Using a magnetic recording medium with an oxidized seed layer, an oxide nickel phosphorus or nickel aluminum seed layer was deposited on a non-magnetic substrate, and combined with doping elements and precision oxidation technology, a dielectric system with excellent crystal orientation and thermal stability was constructed.
It significantly improves the signal-to-noise ratio, data storage reliability and thermal stability of the medium, adapts to the needs of different magnetic recording technologies, and meets the applications in high-temperature environments.
Smart Images

Figure CN120564772A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of magnetic recording media, in particular to a magnetic recording medium with an oxidized seed layer. Background Art
[0002] In magnetic recording technology, as data storage density continues to increase, the requirements for media performance are becoming increasingly stringent. Traditional magnetic recording media often struggle to meet all the requirements simultaneously, facing challenges such as high-density recording, high thermal stability, and high-frequency response. For example, in perpendicular magnetic recording technology, while optimizing the media structure can improve the signal-to-noise ratio and data storage reliability, thermal stability remains insufficient, limiting its application in high-temperature environments. While heat-assisted magnetic recording (HAMR) technology can overcome the superparamagnetic limit by increasing the writing temperature, the thermal stability and thermal management of the media at high temperatures pose new challenges. Furthermore, while shingled magnetic recording (SMR) technology increases storage capacity by increasing track density, adjacent channel interference and write width control issues are becoming increasingly prominent. Meanwhile, while microwave-assisted magnetic recording (MAMR) technology reduces the anisotropy requirements for the media by using microwave fields to assist writing, the high-frequency response characteristics of the media remain a key factor limiting its performance. Summary of the Invention
[0003] An object of the present invention is to provide a magnetic recording medium having an oxidized seed layer, which solves the problems of insufficient thermal stability and insufficient response characteristics.
[0004] To achieve the above-mentioned object, the present invention provides the following technical solution: a magnetic recording medium with an oxidized seed layer, comprising: a non-magnetic substrate;
[0005] a seed layer comprising:
[0006] Oxidized nickel-phosphorus NiP or oxidized nickel-aluminum NiAl, wherein the oxidized NiP contains at least one doping element X having a higher oxidation potential than NiP, and the oxidized NiAl contains at least one doping element Y having a higher oxidation potential than NiAl;
[0007] The doping element X is selected from the group consisting of aluminum, cobalt, chromium, iron, titanium, vanadium, zinc, strontium, lead, sodium and calcium, and the doping element Y is selected from the group consisting of cobalt, iron, titanium, vanadium, zinc, strontium, lead and calcium;
[0008] In the seed layer, the atomic percentage of the doping element X or Y is 0.0002% to 0.5%, and the oxygen content is 50ppm to 500ppm;
[0009] The magnetic layer is located above the seed layer.
[0010] As a preferred embodiment of the present invention, the seed layer has a nanocrystalline structure, and the doping element X or Y is uniformly distributed or gradiently distributed in the oxidized NiP or NiAl, the oxidized NiP contains 60 to 90 atomic % of nickel and 10 to 40 atomic % of phosphorus, and the oxidized NiAl contains 30 to 70 atomic % of nickel and 30 to 70 atomic % of aluminum, and the oxidation potential of the doping element X or Y is higher than -0.10 volts.
[0011] As a preferred embodiment of the present invention, it further comprises a chromium or chromium alloy base layer on the seed layer, a cobalt-chromium intermediate layer on the base layer, and a carbon-containing protective outer coating on the magnetic layer.
[0012] As a preferred embodiment of the present invention, the bottom layer has a thickness of 5-50 nm, the middle layer has a thickness of 2-20 nm, a textured layer is provided between the seed layer and the non-magnetic substrate, the textured layer is titanium nitride or chromium nitride, and the magnetic layer is a cobalt-platinum-chromium-based perpendicular magnetic recording layer with a thickness of 8-25 nm.
[0013] Method for manufacturing a magnetic recording medium with an oxide seed layer:
[0014] Depositing a seed layer, wherein the seed layer is:
[0015] Nickel phosphorus NiP containing a doping element X, wherein the oxidation potential of the doping element X is higher than that of NiP; or nickel aluminum NiAl containing a doping element Y, wherein the oxidation potential of the doping element Y is higher than that of NiAl;
[0016] performing an oxidation treatment on the seed crystal layer, wherein the oxidation treatment is performed in an argon mixed atmosphere containing 5-30 volume % of oxygen, at a treatment temperature of 100-300° C., and for a treatment time of 10-120 seconds;
[0017] A magnetic layer and a protective overcoat layer are sequentially deposited on the oxidized seed layer.
[0018] As a preferred embodiment of the present invention, the seed layer is deposited by physical vapor deposition (PVD) or chemical vapor deposition (CVD) at a deposition rate of 0.1-1 nm / s. Before the oxidation treatment, the deposited seed layer is also subjected to ion etching, the etching gas is argon, and the energy is 100-500 eV.
[0019] As a preferred embodiment of the present invention, it is characterized in that: the above-mentioned doping element X or Y is introduced by co-sputtering or co-evaporation during the deposition process, and its atomic percentage is controlled to be 0.0002% to 0.5%. After the oxidation treatment, the oxygen content in the seed layer is 50 ppm to 500 ppm, and the doping element X or Y forms oxide nanoparticles.
[0020] As a preferred embodiment of the present invention, a chromium or chromium alloy base layer is deposited between the seed layer and the magnetic layer, wherein the base layer is deposited by DC magnetron sputtering and has a thickness of 5-50 nm. The target material for depositing the magnetic layer is a cobalt-platinum-chromium alloy, and the magnetocrystalline anisotropy is optimized by adjusting the platinum content.
[0021] As a preferred solution of the present invention, the protective outer coating is diamond-like carbon DLC, and nitrogen or silane is introduced during deposition for doping modification.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] 1. Through precise composition design and an innovative oxidation process, this invention constructs an oxidized NiP-Al seed layer dielectric system with excellent crystal orientation and thermal stability, significantly improving the performance of magnetic recording media. This system uses magnetron co-sputtering technology to prepare the NiP-Al alloy seed layer, and a two-stage heat treatment process to form a gradient oxidation structure, effectively suppressing the abnormal growth of nickel-phosphorus grains and stabilizing the grain size below 12nm. Combined with the optimized layered structure, it exhibits a high signal-to-noise ratio (SNR) >42dB and excellent data retention reliability, with a coercivity decay rate of only 4.2% over 1000 hours at 85°C / 85% RH.
[0024] 2. This invention has developed a variety of innovative architectures to meet the needs of different magnetic recording technologies, significantly expanding the application scenarios of the media. Through technologies such as oxidized NiAl-V seed layers, Cr-doped NiP oxidized seed layers, and Fe-doped NiAl nanocrystalline oxidized seed layers, the invention achieves high thermal stability (KuV / kBT=85) for heat-assisted magnetic recording (HAMR) media, high-density recording and write width (75nm) and adjacent channel interference suppression (ACI) of -35dB for shingled magnetic recording (SMR) media, and high-frequency response (resonance frequency) of 8GHz for microwave-assisted magnetic recording (MAMR) media, making the media perfectly adaptable to different technology routes. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 Schematic diagram of the layered structure of the present invention; DETAILED DESCRIPTION
[0026] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.
[0027] See also Figure 1 , a magnetic recording medium with an oxide seed layer, comprising a non-magnetic substrate;
[0028] a seed layer comprising:
[0029] Oxidized nickel phosphorus (NiP) or oxidized nickel aluminum (NiAl), the oxidized NiP containing at least one doping element (X) having a higher oxidation potential than NiP, and the oxidized NiAl containing at least one doping element (Y) having a higher oxidation potential than NiAl;
[0030] The doping element (X) is selected from the group consisting of aluminum, cobalt, chromium, iron, titanium, vanadium, zinc, strontium, lead, sodium and calcium, and the doping element (Y) is selected from the group consisting of cobalt, iron, titanium, vanadium, zinc, strontium, lead and calcium;
[0031] In the seed layer, the atomic percentage of the doping element (X) or (Y) is 0.0002% to 0.5%, and the oxygen content is 50 ppm to 500 ppm;
[0032] a magnetic layer located above the seed layer;
[0033] The seed layer has a nanocrystalline structure, and the doping element (X) or (Y) is uniformly distributed or distributed in a gradient in the oxidized NiP or NiAl, the oxidized NiP contains 60 to 90 atomic % of nickel and 10 to 40 atomic % of phosphorus, and the oxidized NiAl contains 30 to 70 atomic % of nickel and 30 to 70 atomic % of aluminum, and the oxidation potential of the doping element (X) or (Y) is higher than -0.10 volts;
[0034] Also included is a chromium or chromium alloy base layer on the seed layer, a cobalt-chromium intermediate layer on the base layer, and a carbon-containing protective outer coating on the magnetic layer;
[0035] The bottom layer has a thickness of 5-50nm, the middle layer has a thickness of 2-20nm, and a textured layer is provided between the seed layer and the non-magnetic substrate. The textured layer is titanium nitride or chromium nitride, and the magnetic layer is a cobalt-platinum-chromium-based perpendicular magnetic recording layer with a thickness of 8-25nm.
[0036] Method for manufacturing a magnetic recording medium with an oxide seed layer:
[0037] Deposit a seed layer, which is:
[0038] Nickel phosphorus (NiP) containing a doping element (X), the doping element (X) having a higher oxidation potential than NiP; or nickel aluminum (NiAl) containing a doping element (Y), the doping element (Y) having a higher oxidation potential than NiAl;
[0039] The seed layer is oxidized in an argon mixed atmosphere containing 5-30% by volume of oxygen at a temperature of 100-300° C. for 10-120 seconds.
[0040] A magnetic layer and a protective overcoat layer are sequentially deposited on the oxidized seed layer.
[0041] The seed layer is deposited by physical vapor deposition (PVD) or chemical vapor deposition (CVD) at a deposition rate of 0.1-1 nm / s. Before oxidation, the deposited seed layer is ion-etched using argon gas at an energy of 100-500 eV.
[0042] The doping element (X) or (Y) is introduced during the deposition process by co-sputtering or co-evaporation, and its atomic percentage is controlled to be between 0.0002% and 0.5%. After oxidation treatment, the oxygen content in the seed layer is between 50ppm and 500ppm, and the doping element (X) or (Y) forms oxide nanoparticles. The method also includes depositing a chromium or chromium alloy base layer between the seed layer and the magnetic layer, the base layer being deposited by DC magnetron sputtering and having a thickness of 5-50nm. The magnetic layer is deposited using a cobalt-platinum-chromium alloy target material, and the magnetocrystalline anisotropy is optimized by adjusting the platinum content.
[0043] The protective outer coating is diamond-like carbon (DLC), which is doped and modified by introducing nitrogen or silane during deposition.
[0044] The specific implementation process of the present invention is as follows: a technical architecture for an oxidized NiP-Al seed layer for perpendicular magnetic recording applications is proposed. The core of the architecture lies in constructing a dielectric system with excellent crystal orientation and thermal stability through precise composition design and innovative oxidation process. The dielectric system uses an aluminum alloy as the substrate. First, a nanoscale surface texture is constructed through ion beam etching (IBE) process. Its surface roughness (Ra) can be controlled to below 0.5nm, laying the foundation for the uniform deposition of subsequent thin films. Subsequently, a 5nm titanium nitride (TiN) film is deposited as a stress buffer layer. Its crystal structure is a NaCl-type face-centered cubic, which can effectively alleviate the thermal expansion coefficient mismatch between the substrate and the seed layer.
[0045] The core innovation is to use magnetron co-sputtering technology to prepare NiP-Al alloy seed layer; by precisely controlling the power of nickel target (99.99% purity), phosphorus target (amorphous red phosphorus) and aluminum target (99.999% purity), Ni 80 P 20-x Al x The typical process parameters are: nickel target power 200W, phosphorus target power 50W (using radio frequency power supply), aluminum target power 10-50W (DC pulse power supply), working pressure 0.5Pa, and deposition rate 0.5nm / s. This composition design enables the aluminum element to form a nanoscale precipitate phase in the NiP matrix, whose chemical formula can be expressed as Ni3(PO4)2·Al2O3 composite oxide.
[0046] During the oxidation stage, an innovative two-stage heat treatment process is employed: First, a pre-oxidation is performed at 200°C for 60 seconds in a 10% O2 / Ar mixed atmosphere (volume ratio), forming a continuous aluminum oxide (Al2O3) passivation layer approximately 2nm thick on the surface. The temperature is then raised to 250°C for 10 seconds for a deep oxidation, allowing oxygen to diffuse into the seed layer, creating an oxygen gradient distribution with a total oxygen content controlled at 300ppm (mass fraction). This gradient oxidation structure (represented as NiP-Al / NiP-Al-O / NiP-O) effectively suppresses abnormal growth of nickel-phosphorus grains, maintaining a stable grain size below 12nm.
[0047] With the subsequent deposition of 20nm chromium (Cr) bottom layer (using DC magnetron sputtering, deposition pressure 0.3Pa, crystal structure is body-centered cubic) and 10nm cobalt chromium (Co 80 Cr 20 ) intermediate layer (pulsed laser deposition, pulse frequency 20Hz, crystal structure is hexagonal close-packed), constructing a perfect (002) texture orientation, and its X-ray diffraction rocking curve half-maximum width (FWHM) is less than 3°; the perpendicular magnetic recording layer uses Co 75 Pt 20 In the Cr5 alloy system, the magnetocrystalline anisotropy field (Hk) was adjusted to 18 kOe by adjusting the platinum content, and the magnetic domain wall energy density (σw) was optimized to 1.2×10 -6 erg / cm; the surface protection adopts a 2nm diamond-like carbon (DLC) film deposited by chemical vapor deposition (CVD), innovatively introducing 5% nitrogen (N2) doping, whose chemical formula can be expressed as DLC:N, which increases the hardness of the film to 35GPa and reduces the friction coefficient to 0.15;
[0048] Accelerated aging tests have shown that after 1000 hours of operation at 85°C / 85% RH, the coercivity (Hc) decay rate of this media is only 4.2%, and the signal-to-noise ratio (SNR) remains above 42dB, perfectly meeting the stringent data storage reliability requirements of enterprise-class hard drives.
[0049] In response to the special requirements of heat-assisted magnetic recording (HAMR) technology for the thermal stability of the medium, this embodiment develops an innovative architecture based on an oxidized NiAl-V seed layer; the medium construction starts with a 30nm Ni on a glass substrate. 50 Al 45 The V5 (atomic percentage) alloy layer is prepared using electron beam co-evaporation technology to achieve precise vanadium doping, with the evaporation rate ratio controlled at NiAl:V=100:1. The oxidation process uses a breakthrough rapid heat treatment in a pure oxygen atmosphere, performing transient oxidation at 300°C for 30 seconds, which selectively enriches oxygen in the grain boundaries, forming a NiAl grain structure encapsulated by VO2 nanophases. Its core-shell structure can be expressed as NiAl@VO2.
[0050] Increase the effective anisotropy field (KuV) to 8.5×10 6 erg / cm 3 Furthermore, the phase change characteristics of VO2 (metal-insulator phase transition occurs at 68°C) achieve thermal expansion coefficient matching within the 180°C operating window, and its thermal expansion coefficient (CTE) remains at 8×10- -6 / ℃; the dielectric functional layer is prepared by oblique angle deposition technology with 25nmCo 75 Pt 25 The multilayer film achieves (111) texture strengthening by adjusting the incident angle (60°-80°), with a texture coefficient (TC) greater than 4.5. Combined with a 12nm gold (Au) heat conduction layer (resistivity 2.2μΩ·cm), it constructs an efficient heat diffusion channel with a thermal conductivity (κ) of 300W / m·K.
[0051] The protection system uses a 3nm diamond-like carbon film deposited by magnetron sputtering, innovatively doped with 10% silane (SiH4). Its chemical formula can be expressed as DLC:Si, which enables the film to maintain excellent oxidation resistance at high temperatures of 300°C, with an oxidation induction time (OIT) of over 200 hours. A specially designed 2nm titanium (Ti) transition layer is achieved through atomic layer deposition (ALD) technology to achieve step coverage, controlling the interface roughness to below 0.3nm, effectively reducing the thermal resistance (Rth) to 5×10 -8 m 2 K / W;
[0052] Measured data show that the dielectric has a thermal stability coefficient (KuV / kBT) of up to 85, can maintain a coercivity of 6000Oe at a write window temperature of 180°C, and has a dielectric noise level (N) of less than 0.5μVrms.
[0053] In order to meet the demand of shingled magnetic recording (SMR) technology for high-density writing of media, this embodiment innovatively develops a Cr element gradient-doped NiP oxide seed layer technology; the medium construction starts with the preparation of a 0.5nm tantalum (Ta) adhesion layer on a NiP-plated aluminum alloy substrate, and then a NiP-Cr gradient layer is deposited using a variable power magnetron co-sputtering system: the Cr content in the bottom area is controlled at 200ppm (0.02at%), and by gradually increasing the Cr target power (linearly increasing from 10W to 50W), it reaches 5000ppm (0.5at%) in the top area, forming a continuous composition gradient distribution, whose chemical formula can be expressed as Ni 80 P 20-x Cr x (x=0.0002-0.005);
[0054] This design gradually reduces the grain size from 15nm at the bottom to 8nm at the top, effectively suppressing the lateral expansion of the magnetic domains and reducing the magnetic domain width (Dw) to below 80nm. The oxidation process adopts a staged treatment strategy: first, low-temperature oxidation at 150°C for 30 seconds forms an oxygen content gradient distribution, and its oxygen concentration curve shows exponential decay. Then, high-temperature treatment at 250°C for 10 seconds increases the total oxygen content to 450ppm, forming a NiP-Cr-O composite oxide layer, whose chemical formula can be expressed as Ni3(PO4)2·Cr2O3.
[0055] The recording layer is made of 12nm Fe 70 Pt 30-x C x The (x=20-40at%) granular film achieves exchange coupling between the soft magnetic phase (FePt) and the hard magnetic phase (Fe3C) by regulating the carbon content, with an exchange coupling field (Hex) of 5000Oe. The protection system adopts an innovative double-layer structure: a 1nm diamond-like carbon layer provides excellent friction performance with a hardness (H) of 25GPa; a 1nm silicon nitride (Si3N4) layer achieves efficient corrosion protection with a corrosion current density (icorr) of less than 1×10 -7 A / cm 2 ;
[0056] The specially designed gradient doping structure narrows the media write width (Ww) to 75nm, achieving an adjacent channel rejection ratio (CTR) of -35dB. After 48 hours of CASS salt spray testing, the surface corrosion area is less than 0.5%. This perfectly balances the conflicting requirements of high-density recording and media stability, making it particularly suitable for consumer-grade, high-capacity mobile hard disk applications.
[0057] In response to the special requirements of microwave-assisted magnetic recording (MAMR) technology for the dynamic response characteristics of the medium, this embodiment proposes an innovative solution based on an Fe-doped NiAl oxide nanocrystalline seed layer; the medium construction begins with chemical mechanical polishing (CMP) of a single-crystal silicon substrate, with the surface roughness (Ra) controlled to below 0.2nm, followed by the deposition of a 2nm titanium nitride (TiN) buffer layer, whose crystal structure is NaCl-type face-centered cubic and the lattice constant (a) is
[0058] Ni was prepared by rapid solidification annealing process 60 Al 35 Fe5 (atomic percentage) nanocrystalline seed layer: by mixing the amorphous alloy with 10 6The material was quenched at a rate of 1000 K / s to obtain a nanostructure with an average grain size of 8 nm. The Fe element segregated at the grain boundaries to form pinning centers, and its chemical formula can be expressed as a NiAl-Fe nanocrystalline composite material. The oxidation process used a low-temperature plasma oxidation system and was carried out for 120 seconds at an oxygen partial pressure of 0.1 Pa. This allowed oxygen to be selectively adsorbed at the grain boundaries, forming a passivation layer with an oxygen content of 80 ppm. The thickness of the oxide layer (tox) was approximately 1 nm.
[0059] This treatment process increases the effective anisotropy field (Hk) to 7.2×10 while maintaining the integrity of the nanocrystalline structure. 6 erg / cm 3 The recording layer uses an innovative SmCo5 / FeCo exchange spring multilayer film structure. By adjusting the ratio of the SmCo5 layer thickness (5nm) to the FeCo layer thickness (3nm), a precise match of the resonant frequency of 8GHz is achieved, and its ferromagnetic resonance linewidth (ΔH) is less than 50Oe.
[0060] The protection system uses atomic layer deposition (ALD) technology to prepare a 1.5nm Al2O3 / DLC composite film, in which the density of the Al2O3 layer reaches 98% and the DLC layer sp 3 Bond content 75%, making the medium at 10 9 After 10 read / write cycles, it still maintains 95% of its initial performance, and its wear rate (K) is less than 1×10 -7 mm 3 / Nm; The actual measurement shows that the coercive force (Hc) of the medium can be adjusted in the range of 4000-8000Oe under the assistance of microwave field, and the peak value of dynamic magnetic permeability μ reaches 1.2, which is the first step for MAMR technology to achieve Tb / in 2 Level surface density provides key dielectric support.
[0061] While embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions, and variations may be made to these embodiments without departing from the principles and spirit of the invention, and that the scope of the invention is defined by the appended claims and their equivalents.
Claims
1. A magnetic recording medium with an oxide seed layer, characterized in that: include: non-magnetic substrate; a seed layer comprising: Oxidized nickel-phosphorus NiP or oxidized nickel-aluminum NiAl, wherein the oxidized NiP contains at least one doping element X having a higher oxidation potential than NiP, and the oxidized NiAl contains at least one doping element Y having a higher oxidation potential than NiAl; The doping element X is selected from the group consisting of aluminum, cobalt, chromium, iron, titanium, vanadium, zinc, strontium, lead, sodium and calcium, and the doping element Y is selected from the group consisting of cobalt, iron, titanium, vanadium, zinc, strontium, lead and calcium; In the seed layer, the atomic percentage of the doping element X or Y is 0.0002% to 0.5%, and the oxygen content is 50ppm to 500ppm; The magnetic layer is located above the seed layer.
2. The magnetic recording medium with an oxide seed layer according to claim 1, wherein: The seed layer has a nanocrystalline structure, and the doping element X or Y is uniformly distributed or distributed in a gradient in the oxidized NiP or NiAl. The oxidized NiP contains 60 to 90 atomic % of nickel and 10 to 40 atomic % of phosphorus, and the oxidized NiAl contains 30 to 70 atomic % of nickel and 30 to 70 atomic % of aluminum. The oxidation potential of the doping element X or Y is higher than -0.10 volts.
3. The magnetic recording medium with an oxidized seed layer according to any one of claims 1 to 2, characterized in that: The invention also includes a chromium or chromium alloy base layer located on the seed layer, a cobalt-chromium intermediate layer located on the base layer, and a carbon-containing protective outer coating layer located on the magnetic layer.
4. The magnetic recording medium with an oxide seed layer according to claim 3, wherein: The bottom layer has a thickness of 5-50nm, the middle layer has a thickness of 2-20nm, a textured layer is provided between the seed layer and the non-magnetic substrate, the textured layer is titanium nitride or chromium nitride, and the magnetic layer is a cobalt-platinum-chromium based perpendicular magnetic recording layer with a thickness of 8-25nm.
5. A method for manufacturing a magnetic recording medium having an oxide seed layer, characterized in that: Depositing a seed layer, wherein the seed layer is: Nickel phosphorus NiP containing a doping element X, wherein the oxidation potential of the doping element X is higher than that of NiP; or nickel aluminum NiAl containing a doping element Y, wherein the oxidation potential of the doping element Y is higher than that of NiAl; performing an oxidation treatment on the seed crystal layer, wherein the oxidation treatment is performed in an argon mixed atmosphere containing 5-30 volume % of oxygen, at a treatment temperature of 100-300° C., and for a treatment time of 10-120 seconds; A magnetic layer and a protective outer coating are sequentially deposited on the oxidized seed layer.
6. The magnetic recording medium with an oxide seed layer according to claim 5, wherein: The seed layer is deposited by physical vapor deposition (PVD) or chemical vapor deposition (CVD) at a deposition rate of 0.1-1 nm / s. Before the oxidation treatment, the deposited seed layer is ion-etched using argon as the etching gas and an energy of 100-500 eV.
7. The magnetic recording medium with an oxidized seed layer according to any one of claims 5 to 6, characterized in that: The doping element X or Y is introduced during the deposition process by co-sputtering or co-evaporation, and its atomic percentage is controlled to be 0.0002% to 0.5%. After the oxidation treatment, the oxygen content in the seed layer is 50 ppm to 500 ppm, and the doping element X or Y forms oxide nanoparticles.
8. The magnetic recording medium with an oxide seed layer according to claim 7, wherein: It also includes depositing a chromium or chromium alloy base layer between the seed crystal layer and the magnetic layer, wherein the base layer is deposited by DC magnetron sputtering and has a thickness of 5-50 nm. The magnetic layer is deposited using a cobalt-platinum-chromium alloy as a target material, and the magnetocrystalline anisotropy is optimized by adjusting the platinum content.
9. The magnetic recording medium with an oxide seed layer according to claim 8, wherein: The protective outer coating is diamond-like carbon DLC, and nitrogen or silane is introduced during deposition for doping modification.